“Come and See” in the Age of Algorithms : Reconfiguring the Johannine Pedagogical Triangle in the Face of Artificial Intelligence - Nomenjanahary Jenny Patrick; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2026)
The rapid integration of generative Artificial Intelligence (AI) into educational institutions introduces profound anthropological, sociological, and theological challenges to traditional formative practices. This study establishes a rigorous interdisciplinary critique of Large Language Models (LLMs) by contrasting modern computational operations with the ancient relational structures found in the first-century Mediterranean world. Utilizing a qualitative, socio-historical, and exegetical methodology anchored in the discipleship recruitment narrative of John 1 :35–51, this research systematically retrieves three foundational Johannine concepts: akoloutheō (existential rupture), menō (intimate, temporal dwelling), and horaō (progressive spiritual vision). These philological elements, contextualized through ancient honor/shame dynamics and social memory theory, are mapped onto Jean Houssaye’s classical pedagogical triangle to diagnose the structural disruptions caused by digital acceleration. The findings reveal a fundamental ontological incompatibility between the relational requirements of authentic human formation and the transactional efficiency of predictive computing. While AI functions effectively as an